Pengembangan E-Learning Berbasis Telegram pada Materi Jas di SMK Negeri 1 Jabon Sidoarjo - Izzah Maulidiyah Yamas; Imami Arum Tri Rahayu; Peppy Mayasari; Mita Yuniati (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The learning process for suit subjects at SMK Negeri 1 Jabon uses two approaches, namely face-to-face learning and virtual learning via WhatsApp groups. However, the existence of innovation in virtual learning is still considered important, including the development of more advanced virtual learning media. This research aims to evaluate the use of Telegram-based e-learning media in suit material as a learning tool, as well as assessing the suitability of the media according to material experts and media experts. This research method is quantitative descriptive using an R&D (Research & Development) approach. Data was collected through a media feasibility questionnaire with a Likert scale from two media experts and two material experts to assess the suitability of Telegram-based e-learning media on material. The results of this research include the development of Telegram-based e-learning media using the Manybot feature to access Botfather, which produces new bots for learning purposes. This Telegram-based e-learning media was considered suitable for use in the learning process and received a good assessment, seen from the average validation results for material experts at 90.05% and media experts at 92.5%, with the title very appropriate and in the good category.